1993
DOI: 10.1126/science.8438157
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oncogenic and Oncogenic Potentials of Interferon Regulatory Factors-1 and -2

Abstract: Interferon regulatory factor-1 (IRF-1), a transcriptional activator, and IRF-2, its antagonistic repressor, have been identified as regulators of type I interferon and interferon-inducible genes. The IRF-1 gene is itself interferon-inducible and hence may be one of the target genes critical for interferon action. When the IRF-2 gene was overexpressed in NIH 3T3 cells, the cells became transformed and displayed enhanced tumorigenicity in nude mice. This transformed phenotype was reversed by concomitant overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
307
3
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 432 publications
(322 citation statements)
references
References 40 publications
9
307
3
3
Order By: Relevance
“…Moreover, transformation mediated by the EGFR derivates HER1 and HER2, a common feature of human tumor cells (Garcia et al, 1997), is also inhibited. Previously, it was shown that IRF-1 can suppress cellular transformation induced by di erent oncogenes, such as myc, fosB (Tanaka et al, 1994b) and IRF-2 (Harada et al, 1993;Futaki et al, 1996). Thus, our results, together with earlier reports, support the de®nition of IRF-1 as a tumor suppressor protein.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, transformation mediated by the EGFR derivates HER1 and HER2, a common feature of human tumor cells (Garcia et al, 1997), is also inhibited. Previously, it was shown that IRF-1 can suppress cellular transformation induced by di erent oncogenes, such as myc, fosB (Tanaka et al, 1994b) and IRF-2 (Harada et al, 1993;Futaki et al, 1996). Thus, our results, together with earlier reports, support the de®nition of IRF-1 as a tumor suppressor protein.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this notion, Harada et al (1993) have shown that balanced expression of IRF-1 and IRF-2, an antagonistic repressor of IRF-1 and IFNb transcription, is critical for normal cell growth. Overexpression of IRF-2 in NIH3T3 cells resulted in transformation and enhanced tumorigenicity of the cells in nude mice, whereas simultaneous overexpression of IRF-1 and IRF-2 reverted this transformed phenotype.…”
Section: Terminal DI Erentiation Negative Growth Control and Myd Genesmentioning
confidence: 64%
“…IRF-2 exhibits both transcriptional activating and repressing activities (Shi et al, 1991). IRF-2 is a critical transacting factor that regulates in vivo responses to LPS and is a potential oncogene (Harada et al, 1993). IRF-2 also has an unexpected role in the regulation of apoptosis and cell growth (Cuesta et al, 2003).…”
Section: Introductionmentioning
confidence: 99%